Múltiplas faces da violência contra mulher imigrante e interseccionalidade : do estado do conhecimento á evidências empirícas no Brasil - Muassinle, Iarissivaia Deolinda Rorigues Muassinle (2021)
Gender-based violence against immigrant women is a field of study that, in recent years, has attracted the interest of researchers, from various scientific areas at a global level. As it is a public health problem, whose prevalence rates tend to increase every year, it is urgent and relevant to understand it. Thus, the aim of this study is to analyze violence against immigrant women in Brazil, based on approaches from the field of Social Psychology and point out relevant theoretical and practical implications in the construction and consolidation of public policies to face this problem. To this end, the research is consolidated through 3 centric articles that: (i) examines the production of scientific knowledge about violence against immigrant women in their multiple contexts. (ii) evaluates evidence of the different types of violence (physical, structural, psychological and cultural) experienced by Haitian immigrant women in Brazil, their potential perpetrators and places of occurrence, based on the framework of Fanon and Gaultung. (iii) examines from the lens of intersectionality how the different conditions of social vulnerability faced by immigrant women in Brazil are reflected in the multiple forms of violence suffered. This is a set of qualitative, review, exploratory and cross- sectional research, using a systematic review method and semi-structured interviews based on the biographical narrative interpretative method, with 16 immigrant women in Brazil, from West African countries, Central and South America. The main results of the research reveal: (i) a view of the state of scientific knowledge on the theme of violence against immigrant women at the global level from 2010 to 2019; (ii) Structural violence is the most prevalent among immigrant women in Brazil, with the Brazilian socio- institutional context being the main aggressor; (iii) due to the life trajectory of the participants from their countries of origin and their experiences in Brazil, there is evidence of physical, psychological and structural violence experiences that overlap in their multiple forms of manifestation and intersectionality of different identities (being a woman , immigrant, black or white, having low socioeconomic status and being obese), which interactively and overlap with each other, constitute conditions of social vulnerability. This research theoretically contributes in the field of social psychology and other human and social sciences, by highlighting the state of global knowledge of scientific research on the theme of violence against immigrant women; by empirically evidencing the multiple forms of violence suffered by immigrant women in Brazil, their manifestations, perpetrating agents and multiplicities of interrelated identities as conditions of vulnerability to the experience of violence. In practice, these evidences may constitute subsidies for the design and improvement of public policies to face this problem.